Irregular-wave impact on lowering of a subsea module with large cavity shells. (1st March 2023) - Guo, Ruinan; Zan, Yingfei; Han, Duanfeng; Wang, Yong; Yuan, Lihao; Qi, Baowen
Abstract: We analyze the dynamics of a complex subsea module while it is being lowered into the splash zone. Experiments are conducted in which a steel-framed subsea module with cavity shells is lowered into the water in the presence of irregular head waves. Numerical simulations of this module are performed based on the Reynolds-averaged Navier–Stokes equations considering irregular waves with the same significant-wave height and spectral peak period as in the experiments. The simulated time series of the cable tension agrees with the experimentally observed envelope. The dynamic tension is obtained in the time and frequency domains by filtering the measured results. The harmonic balance method is used to calculate the dependence of the dynamic mass force coefficients and resistance coefficients on the frequency and depth. The results indicate that there is a larger dynamic effect when the module is semi-submerged, and the peak frequency increases after the semi-submerged state. The frequency and draft have a significant effect on the dynamic coefficients. Highlights: The dynamic response for a lowering operation in an irregular wave is analyzed. Harmonic balance is used to calculate hydrodynamic coefficients for a complex structure. Hydrodynamic coefficients are estimated for a series of continuous lowering phases in irregular waves. Dynamic variables change significantly in the semi-submerged state. Immersion depth and frequency significantly affect the hydrodynamic coefficients.